Development of Android-based learning media on trigonometry for 10th graders - Nikodemus Tanju; Juliana M. H. Nenohai; Patrisius Afrisno Udil (Universitas Sarjanawiyata Tamansiswa, 2024)
One of the main challenges in learning mathematics is bridging students' difficulties in learning abstract material and teachers' weaknesses in presenting the material in an engaging, interactive, and relevant way for students. Technology can be adapted and integrated into mathematics learning activities as an alternative way to overcome these problems. This research aims to develop Android-based learning media on trigonometry material for 10th graders at SMA Negeri 10 Kupang that is valid, practical, and effective. The research and Development (R&D) method with the ADDIE model produced the product. The subject in this study is 10th graders at SMAN 10 Kupang. Interviews, questionaries, and tests were used to collect the data in this research primarily to assess the product's validity, practicality, and effectiveness. The results show that Android-based learning media on trigonometry material is very valid, with an average score of 4,52. The product has also been assessed to be very practical to use by students both in small and large group trials, with the average scores being 4,76 and 4,61, respectively. Android-based learning media is also effective for students learning trigonometry, confirmed by the high percentage of classical completeness in small-group trials (86%) and large-group trials (88%).